Common agricultural policy versus economic and environmental sustainability of agricultural farms in Poland - Smędzik-Ambroży, Katarzyna; Guth, Marta (Wspólna polityka rolna a zrównoważenie ekonomiczne i środowiskowe gospodarstw rolnych w Polsce, 2019)
The purpose of the article was to determine the impact of Common Agricultural Policy (CAP) instruments on the economic and environmental sustainability of farms in Poland in 2004-2014. For this purpose, a panel analysis was used based on farm accountancy data network. It has been shown that agri-environmental subsidies are an instrument that had a positive impact on the economic and environmental sustainability of farms in Poland. In addition, it has been proven that replacing subsidies for agricultural production with single area payments does not favor the increase in the sustainability of agriculture in Poland. In connection with this, agri-environmental subsidies are the most beneficial instrument in the pursuit of increasing the sustainability of agriculture in Poland. From this point of view their importance should be strengthened because they contribute to the implementation of the postulate of increasing the sustainability of the EU agriculture, which is the strategic goal of the European Union
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 10, s. 86-95